Development of 2D Optical Tweezing for Microscopy - Vishnu, K.P. (IISER Mohali, 2020)
Optical tweezers find wide applications in many fields of science. The revolution cre- ated by it’s invention by Arthur Ashkin sparked advance research in the field which led to the development of highly accurate devices for optical trapping. Although other methods are widely researched to develop more precise moving stages, electro- magnetism based devices are often overlooked. These novel moving platform devices have the potential to bring in another revolution in the field of optical tweezing and nanotechnology. The project aims to research on one such device which can potentially give the same accuracy and precision as the high end devices in existence. The approach is to au- tomate the device to see how it function in the μm domain. The project also focuses on developing this idea into an optical tweezer for commercial purposes.
Keywords: 2D Optical; Tweezing; Microscopy